Loop diuretics association with Alzheimer’s disease risk - Graber-Naidich, Anna; Lee, Justin; Younes, Kyan; Greicius, Michael D.; Le Guen, Yann; He, Zihuai (Frontiers in Aging, 2023)
Objectives: To investigate whether exposure history to two common loop diuretics, bumetanide and furosemide, affects the risk of development Alzheimer's disease (AD) after accounting for socioeconomic status and congestive heart failure.Methods: Individuals exposed to bumetanide or furosemide were identified in the Stanford University electronic health record using the deidentified Observational Medical Outcomes Partnership platform. We matched the AD case-cohort to a control cohort (1:20 case:control) on gender, race, ethnicity, hypertension and controlled for variables that could potentially be collinear with bumetanide exposure and/or AD diagnosis. Among individuals older than 65 years, 5,839 AD cases and 116,103 matched controls were included. A total of 1,759 patients (54 cases, 1,705 controls) were exposed to bumetanide.Results: After adjusting for socioeconomic status and other confounders, bumetanide and furosemide exposure were significantly associated with reduced AD risk (respectively, bumetanide odds ratio [OR] = 0.23; 95% confidence interval [CI], 0.15-0.36; p = 4.0×10 -11 ; furosemide OR = 0.42; 95% CI, 0.38-0.47; p < 2.0×10 -16 ).Discussion: Our study replicates in an independent sample that a history of bumetanide exposure is associated with reduced AD risk, while also highlighting an association of the most common loop diuretic (furosemide) with reduced AD risk. These associations need to be additionally replicated and the mechanism of action remains to be investigated.